2016
DOI: 10.1093/humrep/dew183
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between aneuploidy, standard morphology evaluation and morphokinetic development in 1730 biopsied blastocysts: a consecutive case series study

Abstract: No specific funding was obtained for this study. None of the authors have any competing interests to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
210
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(228 citation statements)
references
References 59 publications
11
210
3
4
Order By: Relevance
“…Curiously, t2 is shorter when embryo was incubated in single culture medium than sequential culture medium (27.36 ± 4.12 vs. 29.09 ± 4.86 h) [7]. The mean time of t2 is no significant between euploid (28 h) and aneuploid embryos (28.4 h) [2]. The development of the 2-cell stage may be faster in implanted embryos but no significant in chromosome status.…”
Section: Morphokinetic Markersmentioning
confidence: 95%
See 3 more Smart Citations
“…Curiously, t2 is shorter when embryo was incubated in single culture medium than sequential culture medium (27.36 ± 4.12 vs. 29.09 ± 4.86 h) [7]. The mean time of t2 is no significant between euploid (28 h) and aneuploid embryos (28.4 h) [2]. The development of the 2-cell stage may be faster in implanted embryos but no significant in chromosome status.…”
Section: Morphokinetic Markersmentioning
confidence: 95%
“…In euploid embryos, the mean time of tPNa is 10.2 h and 10.1 h in aneuploid embryos [2]. Therefore, the timing of pronuclear appearance has no significant effect on implantation potential and chromosome status.…”
Section: Morphokinetic Markersmentioning
confidence: 96%
See 2 more Smart Citations
“…They reported no signiicant diference among euploid and aneuploid embryos regarding time-lapse morphokinetics and concluded that morphokinetic parameters can be used in combination with, not instead of, PGS for detecting embryo ploidy status [50]. Conversely, in a retrospective cohort study, a total of 460 embryos were cultured in TLS and biopsied on Day 3.…”
Section: Diferent Studies Based On Time-lapse Observationmentioning
confidence: 99%